The perceived impact of computer technology on the interior design practice - Ang, Lyra Coleen C.; Quevedo, Ma. Teresa P. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
The purpose of this study is to determine the perceived impact of computer technology on the practice of interior design from the perspective of selected interior designers. Data collection included face-to-face semi-structured interviews among fifteen (15) licensed interior designers and instruments such as the background questionnaire, interview questionnaire, and audio recorder were used. Data analysis involved coding methods where significant and recurring ideas in the data were identified first and then grouped into meaningful categories or themes which were further analyzed. Findings show that the computer has taken over almost all of the areas of interior design practice: design, documentation, communication, research, and marketing. The most commonly used application software by the informants were AutoCAD, Google SketchUp, Microsoft Office Package, and the electronic mail. With the integration of computers in the practice, it was established that the computer technology's advantages outweigh its disadvantages. The ease and speed of producing designs, doing revisions, and communication are the most significant benefits identified by the informants. On the other hand, challenges include cost, decline of manual skills, and the constant need to update on the latest application software. Additionally, the threat of illegal practitioners and copying practices are one of the main issues in connection to computer technology. Based on the results of the study, the informants recognize the immense potential of computer technology in the interior design practice. Despite the threats present, all informants demonstrated optimistic views in the integration of computers
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Interior decoration -- Data processing